Treatment pattern among patients with relapsed/refractory multiple myeloma (RRMM) who had received pomalidomide-based regimens in Taiwan - Chieh-Lin Jerry Teng; Su-Peng Yeh; Tsai-Yun Chen; Yu-Chin Hung; Yun-Chu Lin; Sin Syue Li; Ming-Chung Wang; Shang-Yi Huang (Hematology)
Background/purpose The treatment landscape of relapsed/refractory multiple myeloma (RRMM) is rapidly evolving in Taiwan. The present study aimed to assess the treatment patterns among RRMM patients in Taiwan.Methods This retrospective, chart review-based, non-interventional study collected data on RRMM patients (≥20 years old) receiving pomalidomide-based treatment between January 2017 and December 2020 across five sites in Taiwan.Results Median age of the study population was 65.6 years. Approximately 75% patients received a doublet regimen and 25% were on a triplet regimen. Disease progression was the most common cause for switching to pomalidomide-based treatments in doublet (71.2%) and triplet (58.3%) groups. Patients in doublet and triplet groups (>80%) received 4 mg pomalidomide as a starting dose. Overall response rate (ORR: 31.5% and 45.8%) and median progression-free survival (PFS: 4.7 and 6.8 months) were reported in the doublet and triplet regimen. Doublet regimen was discontinued mainly due to disease progression or death (78.1%); however, triplet regimen patients mainly terminated their treatment due to reimbursement limitations (29.2%). Healthcare resource utilization (HRU) was comparable between doublet and triplet groups.Conclusion In Taiwan, half of RRMM patients received pomalidomide-based triplet regimens. Triplet regimens showed a trend towards better outcomes with longer PFS and higher response rates compared to doublets. Notably, the duration of triplet use is influenced by reimbursement limitations. This study provides insight into RRMM treatment patterns in Taiwan and the findings suggest that triplet regimens may be a better alternative than doublet regimens.